italiano (Società e diritti, 2020)
This essay focuses on the violations of one of the most fundamental principles of human rights law throughout the war on terror in the 21st century. Based on a transatlantic perspective, we explored relevant case studies ranging from extraordinary renditions to state secrets and diplomatic assurances. We have also assessed the similarities and divergences between American and European laws and responses to their officials being faced with the irrefutable proof of having violated the prohibition of torture throughout their quest in combating terrorism.